The hygrothermal degradation of PET in laminated multilayer. (February 2017) - Dubelley, Florence; Planes, Emilie; Bas, Corine; Pons, Emmanuelle; Yrieix, Bernard; Flandin, Lionel
Graphical abstract: The combination of macroscopic and microscopic IR permitted to study the PET hydrolysis in multilayer. Reflecting the orientation effects in IR spectroscopy, a kinetic degradation can be established with two markers characteristics of chemistry (COOH) and crystallinity changes. Highlights: Methodology to track by IR the PET degradation regardless of its orientation. Accurate data treatment of massive number of IR spectra. High spatial resolution of hygrothermal degradation in thin PET layered structure. DSC, IR markers reveal gradual rise of 15% in crystallinity tied to COOH formation. Surprisingly, the 3 PET layers show similar degradation levels in severe conditions. Abstract: This study concerns a multilayer film made with three PET layers coated with evaporated aluminum and a sealant material used for Vacuum Insulation Panels in severe conditions (70 °C and 90%RH). The main goal was to determine the mechanism responsible of the multilayer degradation in order to improve the durability. In order to understand the chemical changes, the different PET layers were analyzed by FTIR spectroscopy coupled with microscopy. Firstly, this work overviews all former assignments of the infrared bands for PET polymer, together with a classification of each band according to its sensitivity to crystallization, orientation and chemical degradation. Then the study of PET outer layer by IR spectroscopy led to the identification of series of aging markers characteristic of the polymer hydrolysis: formation of oxidation products, evaluation of crystallinity correlated to molecular weight. A kinetic hydrolysis of PET can be established until 870 days in continuous conditions of aging. The degradation on a chemical point of view became significant after 400 days. Finally, the combination of macroscopic and microscopic FTIR permitted to determine the changes in each individual layer both in chemistry and crystallinity point of view. Surprisingly, the three PET layers in the multilayers over go similar degradation in severe hydrolysis.